2020
DOI: 10.1002/apj.2550
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis, dielectric properties of barium titanate, cobalt doped barium titanate, and their graphene nanoplatelet composites

Abstract: In this work, pure barium titanate (BT) and cobalt doped barium titanate (CBT) were synthesized by using barium chloride, tetrabutyl titanate, cobalt chloride, and titanium chloride as precursors via a two-step hydrothermal process. These precursor mixtures were further blended with a dispersion of surfactant + graphene nanoplatelets (GNP) judiciously during the second step of hydrothermal process to obtain their respective BT-GNP and CBT-GNP nanocomposites. The morphological and crystal structures of BT, CBT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This difference induces a lattice strain, according to Mahmoud et al [90], and significantly causes the shrinkage of the optical bandgap, as manifested by absorption red shifting in the UV spectra. 5) [91]. Therefore, the obtained results are in good agreement with those of the X-ray diffraction analysis.…”
Section: Quantitative Pxrd Analysissupporting
confidence: 87%
“…This difference induces a lattice strain, according to Mahmoud et al [90], and significantly causes the shrinkage of the optical bandgap, as manifested by absorption red shifting in the UV spectra. 5) [91]. Therefore, the obtained results are in good agreement with those of the X-ray diffraction analysis.…”
Section: Quantitative Pxrd Analysissupporting
confidence: 87%
“…34 When compared to PbTiO 3 , the data from the absorbance curves of (Pb 0.8 La 0.2 )(Ti 0.9 Ni 0.1 )O 3 revealed that, independently of the sintering temperature, the substitution of Ti 4+ by Ni 2+ decreased the band gap, as theoretically predicted for Pb(Ti,Ni)O 3-δ 6,8 and observed in some works. 1,2,[35][36][37] Although our composition is nominally charged neutral, our data show that the replacement of Ti 4+ by Ni 2+ is the main contribution to narrow the band gap, in comparison to the parent PbTiO 3 .…”
Section: Resultsmentioning
confidence: 76%
“…2,3 Barium titanate nanoparticles are widely used to make small, high-capacity microcapacitors and temperature-compensating components; 4,5 as well as nonlinear components, dielectric ampliers, memory components for electronic computers, ceramic sensitive components, microwave ceramics, and piezoelectric ceramics. 6,7 In recent years, with the continuous development of the electronics industry, the demand for BaTiO 3 -based ceramics has been increasing; and higher requirements for BaTiO 3 purity, particle size, crystal shape, and dispersion have been proposed. 1,8 There is broad utility in preparing high-purity, ultrane BaTiO 3 powder.…”
Section: Introductionmentioning
confidence: 99%